Surfactant-assisted synthesis of MgO: Characterization and catalytic activity on the transesterification of dimethyl carbonate with glycerol - Simanjuntak, Fidelis Stefanus Hubertson; Lim, Seung Rok; Ahn, Byoung Sung; Kim, Hoon Sik; Lee, Hyunjoo (ELSEVIER SCIENCE BV, 2014)
Various forms of MgO were synthesized and used as catalysts in the transesterification of dimethyl carbonate (DMC) with glycerol for the synthesis of glycerol carbonate (GLC). MgO synthesized using a surfactant (a triblock copolymer of ethylene oxide/propylene oxide/ethylene oxide, known as Pluronic F127) showed a much higher GLC yield of 75.4% compared to other MgO catalysts synthesized without using a surfactant at reaction conditions of 90 degrees C, DMC/glycerol = 2, and catalyst/glycerol = 5 wt%. With an increase of the weight ratio of the surfactant/Mg precursor, the catalytic activity was increased. However, the activity did not change substantially when the surfactant/Mg precursor ratio was greater than 5. The high catalytic activity of MgO prepared with the surfactant (MgO-S) is attributed to the higher basic site concentration on the surface. This originated from low-coordination oxide ions at the corner sites (O-3c(2-)), as shown in the basic site titration and UV-diffuse reflectance analysis results. It is also noted that MgO-S could be easily recovered after the reaction and reused at least five times without serious catalyst deactivation. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: MAGNESIUM-OXIDE; NANOCRYSTALLINE MGO; INORGANIC MATERIALS; HYDROXIDE; SIZE; NANOSTRUCTURES; BIODIESEL